Perkembangan Kualitas Pembiayaan Bank Syariah di Indonesia: Tren Kategori dan Non-Performing Financing 2015–2024 - Siyamto, Yudi (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study analyzes the development of Islamic banking financing quality in Indonesia during the period 2015–2024, focusing on the distribution of financing categories and the dynamics of the Non-Performing Financing (NPF) ratio. Secondary data were obtained from the Islamic Banking Statistics published by the Financial Services Authority of Indonesia (OJK). A descriptive quantitative method with time-series trend analysis was applied to map the shifts in the proportions of five financing categories: current, special mention, substandard, doubtful, and loss. The findings indicate that the current category consistently dominated more than 85% of financing throughout the observation period, reflecting the stability of Islamic banks’ portfolios. These results highlight that sustaining the dominance of current financing must be accompanied by stronger mitigation strategies for problematic financing, particularly loss financing, in order to safeguard industry resilience. The novelty of this research lies in its use of a full decade of longitudinal data, offering a more comprehensive perspective compared to prior studies that typically focused on shorter periods. The practical implication of this study is the urgency of strengthening risk management, improving governance, and ensuring sustained regulatory support to maintain the stability of Indonesia’s Islamic banking sector.